Suppresor Mutations Derived from the Most Severe Protein Folding Mutation Known - Jameasekowalcyzk, Rhonda; Liberatorre, Katia Angélica; Villafañe, Robert J. (Puerto Rico Health Sciences Journal, 2014)
see manuscript